2000
DOI: 10.1136/adc.83.3.234
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the supine and prone position on diaphragm thickness in healthy term infants

Abstract: Background-The physiological basis underlying the decline in the incidence of sudden infant death syndrome (SIDS) associated with changing the sleep position from prone to supine remains unknown. Aims-To evaluate diaphragm thickness (t di ) and shortening in healthy term infants in the prone and supine positions in order to determine whether changes in body position would aVect diaphragm resting length and the degree of diaphragm shortening during inspiration. Methods-In 16 healthy term infants, diaphragm thic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
29
1

Year Published

2002
2002
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(35 citation statements)
references
References 30 publications
5
29
1
Order By: Relevance
“…The noninvasive feature of ultrasonography makes it well suited for the study of neonatal diaphragm (12,19,20). Our findings that 1) t di at end-expiration is positively associated with BW and BL and 2) calculated diaphragm strength is independent of length and weight are similar to what we previously found in adults.…”
Section: Discussionsupporting
confidence: 91%
“…The noninvasive feature of ultrasonography makes it well suited for the study of neonatal diaphragm (12,19,20). Our findings that 1) t di at end-expiration is positively associated with BW and BL and 2) calculated diaphragm strength is independent of length and weight are similar to what we previously found in adults.…”
Section: Discussionsupporting
confidence: 91%
“…22 The postulated effect of the prone posture on diaphragmatic function in healthy term neonates 20 is not supported by either our findings of a higher PIMAX in the supine compared with the prone posture or postural differences in diaphragm configuration recently described in healthy term neonates. 10 Using ultrasonographic examination, Relian et al 10 showed that the diaphragm was significantly thicker at end expiratory volume in the prone than in the supine posture. In addition, the prone posture was associated with greater diaphragm thickening during inspiration.…”
Section: Discussionmentioning
confidence: 99%
“…9 Changes in posture by alterations in respiratory system mechanics or lung volume could affect diaphragm function by influencing the resting length of the diaphragm or the degree to which it shortened during inspiration. 10 We therefore hypothesised that any posture related changes in oxygenation in convalescent infants could be explained by alterations in respiratory muscle strength. The aims of two consecutive studies were to test that hypothesis.…”
mentioning
confidence: 99%
“…The hypothesis that prone position overburdens the diaphragm was investigated by Rehan et al within a study that included 16 healthy children [18]. This study showed that in this position the diaphragm is much thinner and shorter at the endings of inspiratory and expiratory lung volume.…”
Section: Discussionmentioning
confidence: 99%